Digital Infrared Thermographic Imaging for Limb Salvage in Patients at Risk of Amputation: Prospective Observational Study - Víctor Manuel Loza-González; Eleazar Samuel Kolosovas-Machuca; Patricia Aurea Cervantes-Báez; José Luis Ramírez-GarcíaLuna; Edgar Guevara; Mario Aurelio Martínez-Jiménez (JMIR Formative Research)
Abstract BackgroundScores and prediction models such as the mangled extremity severity score (MESS) for trauma and the Wound, Ischemia, and foot Infection (WIfI) classification for diabetic foot ulcers help in the decision-making process for amputation. However, these tools can be subjective as they depend on the experience of the medical staff applying them. ObjectiveThis study aimed to assess the impact of temperature measurement using infrared thermal imaging in extremity salvage in patients at risk of limb amputation. MethodsWe included 29 patients who sought a second opinion after an amputation recommendation. Infrared thermographic images were acquired to measure the temperature difference (ΔT) between the injured and uninjured limbs. For patients with salvaged limbs, we provided clinical follow-up for up to 12 weeks. ResultsOf the 29 patients enrolled in the study, 27 limbs were salvaged. Thermographic imaging allowed the distinction into two groups: the first group of 18 patients with mean ΔT value of −3.6 °C (SD 1.99 °C) , and the second group of 9 patients with mean ΔT of 3.36 °C (SD 2.71 °C). None of the patients in either group showed progression in ΔT values within the first 5 days; at the twelfth week, ΔT values approached 0 °C at wound closure. Of the two patients who required amputation, one showed an initial ΔT of −4.3 °C, which worsened to −5 °C by the fifth day, and the other patient showed an initial ΔT of −4.5 °C, which worsened to −5.8 °C by the fifth day. ConclusionsDigital infrared thermography is a tool that may help guide limb salvage in patients with uncertain clinical diagnoses. This imaging modality allows visualization of thermal differences and patterns derived from thermal changes in patients at risk of limb amputation.